Neurological Disease in Lupus: Toward a Personalized Medicine Approach - McGlasson, Sarah; Wiseman, Stewart; Wardlaw, Joanna; Dhaun, Neeraj; Hunt, David P. J. (Frontiers in Immunology, 2018)
The brain and nervous system are important targets for immune-mediated damage in systemic lupus erythematosus (SLE), resulting in a complex spectrum of neurological syndromes. Understanding and classifying nervous system disease in lupus pose significant challenges. Among the difficulties to be addressed are a diversity of clinical manifestations and a lack of understanding of their mechanistic basis. However, despite these challenges, progress has been made in our understanding of the pathways which contribute to neurological disease in SLE. Understanding the molecular pathogenesis of neurological disease in lupus will inform both classification and approaches to clinical trials.